Target Markets – International Terrorism Meets Global Capitalism in the Mall - Suzi Mirgani (transcript, 2017)
This book explores the points of convergence between corporate capitalist and terrorist practice. Assessing an increase in the number of terrorist attacks directed at commercial entities in urban areas, with an emphasis on the shopping mall in general and Nairobi's Westgate Mall in particular, Suzi Mirgani offers a fascinating and disturbing perspective on the spaces where the most powerful forces of contemporary culture – the most mainstream and the most extreme – meet on common ground.